2017
DOI: 10.1002/chem.201703164
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Transition Metal Sulfides Anchored on Amorphous Carbon‐Coated Multiwalled Carbon Nanotubes for Enhanced Lithium‐Ion Storage

Abstract: Cobalt sulfide and molybdenum sulfide, with high theoretical capacities, have been considered as one of most promising anode materials for lithium-ion batteries (LIBs). However, the poor cyclability and low rate performances originating from the large volume expansion and poor electrical conductivity extremely inhibit their practical application. Here, the electrochemical performances are effectively improved by growing amorphous cobalt sulfide and molybdenum sulfide onto amorphous carbon-coated multiwalled ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 64 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…3,20 Through reducing the particle size of MoS 2 into the nanometer scale, the diffusion distance of Li + /Na + ions can be effectively shortened, thereby accelerating the reaction kinetics. Another strategy is to form MoS 2 /carbon-based nanocomposites with a special design to partly enhance the electrochemical properties of alkali metal ion batteries, such as MoS 2 /graphene networks, 21,22 CNTs@C@MoS 2 nanoarchitectures, 23 bowl-like C@MoS 2 nanocomposites, 24 hierarchical MoS 2 /N-doped carbon nanobelts, 25 MoS 2 @hollow carbon spheres, 26 etc. However, although this combination method can solve the problems of electrode conductivity and structural degradation, in most cases, the MoS 2 is usually loaded on the surface of the substrate, which is in direct contact with the electrolyte and suffers from drastic aggregation and unwanted side reactions during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…3,20 Through reducing the particle size of MoS 2 into the nanometer scale, the diffusion distance of Li + /Na + ions can be effectively shortened, thereby accelerating the reaction kinetics. Another strategy is to form MoS 2 /carbon-based nanocomposites with a special design to partly enhance the electrochemical properties of alkali metal ion batteries, such as MoS 2 /graphene networks, 21,22 CNTs@C@MoS 2 nanoarchitectures, 23 bowl-like C@MoS 2 nanocomposites, 24 hierarchical MoS 2 /N-doped carbon nanobelts, 25 MoS 2 @hollow carbon spheres, 26 etc. However, although this combination method can solve the problems of electrode conductivity and structural degradation, in most cases, the MoS 2 is usually loaded on the surface of the substrate, which is in direct contact with the electrolyte and suffers from drastic aggregation and unwanted side reactions during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ac omposite materialc omposed of carbonm aterial and at in-based alloy is often used as the anode material for lithium-ion batteries. [43][44][45][46] In this work, we have developed an effective and easy hydrothermal method to combine SnSe 2 and carbon nanotubes into aS nSe 2 /CNTsh ybrid nanostructure. [32][33][34][35][36] Like other kinds of IV-VI binarys emiconductor nanocrystals (NCs), SnSe 2 crystallizes in ah exagonal lattice with av an der Waals distance separatingt he (001) planes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cylindrical structure of carbon nanotubes does not collapse after repeatedc harge and discharge cycles, which can significantly enhance electrochemical performance, especially the cycle life of batteries. [43][44][45][46] In this work, we have developed an effective and easy hydrothermal method to combine SnSe 2 and carbon nanotubes into aS nSe 2 /CNTsh ybrid nanostructure. In this structure, ac ylindricalt hreadlet of carbon nanotubes prevents it from collapsing after long cycles,a nd large interlayer spacing is advantageous for the fast intercalation/de-intercalation of lithium ions.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum sulfide, one of the most prospective alternatives to the noble metal Pt cocatalyst, has widely been used in the field of photocatalytic H 2 production. Its basic principle of enhancing H 2 production is that the unsaturated S atoms of molybdenum sulfide can quickly capture protons (H + ) in the solution and then accelerate the interfacial H 2 -production reaction. , However, it is difficult to obtain high H 2 -production performance of molybdenum sulfide owing to its weak conductivity and limited active sites. , Recently, many studies have reported that constructing molybdenum-based bimetallic sulfide is one of the most significant and effective methods to optimize its electronic and surface structures for enhanced electrocatalytic H 2 -production activity. For example, Wu et al found that, compared with CoS and MoS, CoMoS nanosheets possessed higher electrocatalytic H 2 -evolution performance due to the formation of porous, defect-rich, and vertically aligned nanostructure.…”
Section: Introductionmentioning
confidence: 99%